The Adoption and Readiness of Digital Technologies Among Auditors in Public Accounting Firms: A Structural Equation Modeling Analysis - Hendra Susanto; Agus Joko Pramono; Bahrullah Akbar; Suwarno Suwarno (Research Horizon, 2023)
This research aims to investigate the influence of auditors' optimistic and innovative attitudes on their intention to conduct audits using Computer-Assisted Audit Techniques (CAATs). The study adopts a quantitative approach and gathers data from 224 respondents employed in 20 Public Accounting Firms located in Central Java, selected through random sampling techniques. Structural Equation Modeling (SEM) is employed for data analysis. The research findings reveal that auditors' optimistic and innovative attitudes have a positive and significant impact on their perceived ease of use of CAATs and their perception of improved performance when utilizing CAATs in conducting audits. These positive perceptions subsequently influence the auditors' intention to adopt and incorporate CAATs in their audit practices. The results of this study contribute valuable insights into the importance of auditors' attitudes in shaping their intention to adopt CAATs, emphasizing the significance of positive attitudes towards technological innovations in the audit profession. These findings hold implications for audit firms and professionals, highlighting the need to foster optimistic and innovative mindsets to facilitate the integration of CAATs into audit practices effectively. This research provides a foundation for further studies in the domain of audit technology adoption and underscores the significance of fostering a forward-thinking culture within the audit profession to enhance the use of CAATs and optimize audit performance.